Effect of Feeding Materials on Yield, Quality of Vermicompost, Multiplication and Reproduction of Eisenia Foetida - Chaulagain, Anon; Maharjan, Biboss; Pathak, Rajiv; Piya, Shristi; Chimoriya, Sharmila; Shrestha, Inisa; Gauchan, Dhurva P.; Lamichhane, Janardan (Kathmandu University Journal of Science, Engineering and Technology, 2018)
The most promising earthworm species used for vermicomposting is Eisenia foetida for their tolerance in wide range of moisture levels and temperatures. The earthworms (E. foetida) were grown in cow dung wastes and cow dung wastes supplemented with plant materials of banana pseudo-stem, leaf litter and sawdust respectively. The earthworm population, cocoon number, vermicompost amount, macronutrient contents (N, P, and K), microbial population, pH and electrical conductivity were examined to assess the effect of animal waste (cow dung) and plant material mix on multiplication, reproduction, yield and vermicompost qualities of E. foetida. The multiplication and reproduction were achieved highest in the mixture of cow dung and sawdust vermicompost and lowest in the mixture of cow dung and banana pseudo-stem vermicompost. But the amount of vermicompost was found to be highest in cow dung as sole source of feeding material as compared to the cow dung mixed with plant materials. High quality vermicompost containing nitrogen, phosphorus, potassium and greater microbial population was produced from the mixture of cow dung and banana pseudostem vermicompost as compared to other mixtures. All these vermicomposts showed acceptable level of pH and electrical conductivity values.Kathmandu University Journal of Science, Engineering and TechnologyVol. 13, No. 2, 2017, page: 15-25